The Implementation of Voice Note on WhatsApp for Teaching Speaking English - Aryanata, I Made Wahyu Aryanata; Padmadewi, Ni Nyoman; Utami, I Gusti Ayu Lokita Purnamika (English Education Department STKIP Agama Hindu Singaraja, 2022)
This study aims to find out how teachers apply voice notes to teach speaking skills at SMA Candimas Pancasari through recount text topics. This research uses the descriptive qualitative method. In this study, the data obtained through observation, interview, and questionnaire methods were analyzed descriptively. The researcher used purposive sampling to select the research subject, of which there was 1 English teacher and 77 students who had been researched by researchers to be observed, interviewed, and given a questionnaire. The results showed that the implementation of voice notes can be done through six steps in pre-activity, main-activity, and post-activity. Related to its’ implementation, the teacher also encountered several challenges, namely internet connection, low participation, students' lack of vocabulary, poor access in remote areas, and teacher difficulties in evaluating students' assignments. In addition, students gave positive opinions on the implementation of voice notes on WhatsApp in class, it can be proven where students dominantly choose